Efek Analgesik Kombinasi Kurkumin dan Parasetamol pada Mencit yang Diinduksi Asam Asetat menggunakan Isobologram (The Analgesic Effect of Combination of Curcumin and Paracetamol in Acetic acid-induced Mice using Isobolograms) - Nugroho Priyo Utomo; Cicih Komariah; Yudha Nurdian (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Paracetamol is a drug that classified as NSAID and commonly used as analgesic agent. These drugs have toxic effects that lead to liver damage. This effects caused by accumulation the metabolite compound of paracetamol, N-acetyl-p-benzoquinone (NAPQI), by cytochrome P450 enzyme. Some studies reported that curcumin have analgesic effects and inhibit action of cytochrome P450 enzyme. The purpose of this study was to determine the analgesic effect of curcumin and paracetamol combination in 27 acetic-acid induced mice. The result of this study showed that 2358,815 µg of curcumin and paracetamol combination can inhibit pain up to 50%. This result is smaller than paracetamol that need 4200 µg to achieve the same pain inhibition. One Way Annova test showed siginificant difference between paracetamol group and combination group. Isobolographic analysis results showed curcumin and paracetamol have synergistic properties in mice acetic-acid induced pain. Keywords: curcumin, paracetamol, isobolograph